2020
DOI: 10.1101/2020.07.11.20147157
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of environmental factors on severity and mortality of COVID-19

Abstract: Background Most respiratory viruses show pronounced seasonality, but for SARS-CoV-2 this still needs to be documented. Methods We examined the disease progression of COVID-19 in 6,911 patients admitted to hospitals in Europe and China. In addition, we evaluated progress of disease symptoms in 37,187 individuals reporting symptoms into the COVID Symptom Study application. Findings Meta-analysis of the mortality risk in eight European hospitals estimated odds ratios per one day increase in the admission date t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 48 publications
3
24
0
2
Order By: Relevance
“…There are previous studies that associate temperature, solar radiation, wind speed or rainfall with COVID-19 cases or deaths in different regions ( Bashir et al, 2020a ; Guasp et al, 2020 ; Kifer et al, 2020 ; Liu et al, 2020 ; Luo et al, 2020 ; Pequeno et al, 2020 ; Rosario et al, 2020 ; Tosepu et al, 2020 ; Wang et al, 2020 ). However, generally there are contradictory and/or inconclusive findings.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are previous studies that associate temperature, solar radiation, wind speed or rainfall with COVID-19 cases or deaths in different regions ( Bashir et al, 2020a ; Guasp et al, 2020 ; Kifer et al, 2020 ; Liu et al, 2020 ; Luo et al, 2020 ; Pequeno et al, 2020 ; Rosario et al, 2020 ; Tosepu et al, 2020 ; Wang et al, 2020 ). However, generally there are contradictory and/or inconclusive findings.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding weather conditions, there are several studies that have been published during recent months reporting negative correlation between temperature and COVID-19 cases (see for example Luo et al, 2020 ; Pequeno et al, 2020 ; Wang et al, 2020 ), humidity and death counts ( Ma et al, 2020 ) or rainfall and new daily cases ( Menebo, 2020 ). A recent study followed almost 7000 hospitalized patients from Europe and China and reported that the increase in ambient temperature is linked to less severe symptoms ( Kifer et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The above studies show that humidity acts not only as a non-pharmaceutical intervention for influenza but furthermore, in a sense, the surrounding water can be regarded as antiviral against the enveloped viruses [20], [23]. Viral envelope proteins from a variety of human pathogens including SARS, HIV-1, and influenza virus are extensively glycosylated [24], [25].…”
Section: Introductionmentioning
confidence: 94%
“…(Casanova et al, 2010) It was suggested that the coronaviruses transmit more easily during cold weathers. (Kifer et al, 2020) Even in the case of SARS-COV-2, meteorological factors seem to influence the spread of the virus. (Xu et al, 2020) It was observed that the highest outbreaks were in colder regions when Assuming that different climatic conditions affect transmission of SARS-COV-2 differently, it is important to find the association between minimum temperature, maximum temperature, average temperature, precipitation and COVID-19 incident cases and COVID-19 deaths.…”
Section: Introductionmentioning
confidence: 99%